OPTIMALISASI IN OUT BARANG LOGISTIK DENGAN SISTEM RFID - Igo Permana; Ruby Galuh Septiono; Budiantoro; Besar Agung Martono (Prosiding SEMANIS: Seminar Manajemen Bisnis, 2023)
Technological advances in the industry are currently growing rapidly, in increasing the speed of time in and out of goods and accurate data in the logistics area requires a system that can automatically detect and store integrated data. The use of identification technology can simplify the coding system. Identification technology used is RFID (Radio Frequency Identification). RFID is a method that can be used to store or receive data remotely using a device called an RFID tag. The purpose of this research is optimizing the entry and exit system of goods with RFID technology, designing hardware and software supporting the RFID Logistics System. From the implementation, it is concluded that RFID is one of the tools needed in data reading automation activities to anticipate human error in the goods entry and exit system. With the development of a Logistics System supported by RFID, it is hoped that the speed and accuracy of transaction data can be achieved so that it can help companies